Empowering Urban Sustainability Through Higher Education: A Strategic Framework for Student-Driven Initiatives at Istanbul Gelisim University - Oluwagbemiga Paul Agboola; Hourakhsh Ahmad Nia; Abdulaziz Alsharif; Murat Arapoğlu (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2025)
University campuses serve as critical infrastructures within specific regions, playing a pivotal role in the development of surrounding communities by fostering knowledge dissemination and contributing to the establishment of knowledge clusters.  This study explores the impact of Istanbul Gelisim University’s sustainability initiatives, focusing on student engagement, strategic planning, collaboration, and innovation as key drivers of urban sustainability. Using structured questionnaires, the research gathers quantitative data on students’ perceptions and identifies barriers, opportunities, and strategies for enhancing sustainability efforts on campus. It proposes an integrated framework combining current practices with innovative, actionable steps to guide sustainable campus development. Emphasising alignment with the UN Sustainable Development Goals (SDGs), the study highlights the university’s role in minimising environmental impact and promoting inclusive stakeholder participation. Key recommendations include forming a sustainability committee, launching awareness campaigns, conducting energy audits, and initiating waste reduction programs. Long-term goals suggest investing in renewable energy, incorporating sustainability into infrastructure planning, and supporting sustainability-focused research. This approach positions Gelisim University as a model for sustainability in higher education, demonstrating how education, collaboration, and practical initiatives can address urban sustainability challenges and empower students to contribute meaningfully to a sustainable future.